Perkembangan Tari Asaik Dilihat Dari Aspek Kegunaan dan Fungsi di Desa Paling Serumpun Kecamatan Hamparan Rawang Kota Sungai Penuh - Intan Milanda; Indrayuda Indrayuda (Journal of Creative Student Research, 2023)
This study aims to describe the development of Asaik Dance which is seen from the aspects of use and function in the past and present in the most cognate village, Hamparan Rawang District, Sungai Penuh City. This type of research is qualitative research with descriptive methods. The main instruments in this study are the researchers themselves and are assisted by supporting instruments such as, stationery, video and photo cameras, tape recorders. Data collection techniques are carried out by means of observation, interviews, and documentation. The steps to analyze the data are data that has been successfully collected from the results of observations, interviews and reduced documentation and then presented and verified. The results showed that the development of Asaik Dance was seen from the aspects of usefulness and function in the past and in the present, nothing has changed, such as the use of dance for traditional medicine, namely medicine, which serves to overcome the problem of ghaib disease, or non-medical diseases. Although Islam has developed, this dance is still used and functioned as in the past.